Studi Pengaruh Batas Atterberg Terhadap Kuat Geser Tanah Ekspansif dan Non Ekspansif - Cikmit, Arlyn Aristo; Sudisman, Rangga Adiprima; Hidayat, Wirman; Guritno, Bagus; Andhika, Muhammad Brianjaya (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2024)
The shear strength test of expansive clay is commonly conducted with the initial water content close to its optimum moisture content, obtained from the compaction test. However, the initial water content of natural soil is most likely close to its plastic limit, liquid limit, or somewhere in between. This study aims to report the results of undrained shear strength tests on expansive and non-expansive soils with the initial water content at its Atterberg limit. Two types of expansive soil and a non-expansive soil were tested with water content variations of ±5% PL and ±5% LL. The shear strength tests were conducted using the laboratory vane shear test (LVS) and a direct shear test. Results indicate that the undrained shear strength significantly decreased with the higher initial water content; however, the ratio of shear strength decrement of expansive soil (95%) was higher than that of non-expansive soil (89%).